Change of the economic model of Russia’s development as a response to the new geo-economic reality - V. I. Filatov; S. A. Pobyvaev (Мир новой экономики)
The sanctions war against Russia unleashed by Western countries led by the United States forms a new geopolitical reality for the country. In fact, an economic war has been declared against Russia, the main instruments of which are the country’s cut off from the global financial system, the closure of the most important markets for the Russian main export products and the embargo on the machinery and equipment import to the country, which is essential for various sectors of the Russian economy. The sanctions imposed on the country pose both short-term and long-term threats. The first ones are associated with the degradation of the current economic situation, but can be overcome within a few years. The other ones may have delayed but deeper negative consequences for the economy, as they are aimed at undermining its technological competitiveness and investment process, thus increasing the threat of the prolonged stagnation of the national economy. Overcoming such threats takes a long time and transformation of the country’s export-oriented raw material model of the economy based on the activation of structural, scientific, technological and investment policy. The article discusses possible approaches to the implementation of such a transition.